DETERMINANTS OF IRON AND FOLIC ACID SUPPLEMENTATION ADHERENCE AND ITS IMPACT ON ANEMIA AMONG PREGNANT WOMEN: A SYSTEMATIC LITERATURE REVIEW : ANEMIA AMONG PREGNANT WOMEN - Elsa Widyavihusna; Idral Purnakarya; Azrimaidaliza Azrimaidaliza (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2026)
Background: Anemia in pregnant women remains a major global public health problem, particularly in developing countries, including Indonesia. One of the primary interventions to prevent anemia is iron supplementation. However, the effectiveness of this intervention is highly dependent on adherence to iron tablet consumption among pregnant women. This study aims to analyze the determinants of adherence to iron supplementation and its impact on anemia through a synthesis of international and national studies. Methods: The method used was a literature review of five reputable scientific articles with cross-sectional and case-control designs. The analysis was conducted using a descriptive narrative approach with thematic synthesis focusing on determinants and anemia outcomes.Results: The results show that adherence to iron supplementation remains low, with an average below 50%. The main determinants include maternal education, socioeconomic status, antenatal care (ANC) visits, access to healthcare services, and exposure to health information. In addition, program-related factors such as social assistance and the quality of healthcare services also play a role. Adherence to iron supplementation has been shown to significantly reduce the risk of anemia, with an estimated reduction of more than 25%.Conclusion: It can be concluded that anemia in pregnancy is a multifactorial problem influenced by individual, social, and healthcare system factors. Interventions to improve adherence should be carried out comprehensively through education, strengthening ANC services, and optimizing community-based health programs.